2018
DOI: 10.1111/sji.12680
|View full text |Cite
|
Sign up to set email alerts
|

The complement lectin pathway after cardiac arrest

Abstract: The lectin pathway (LP) of the complement system may initiate inflammatory reactions when body tissue is altered. We aimed to investigate levels of the LP proteins in out-of-hospital cardiac arrest patients, and to compare these with healthy individuals. Furthermore, we aimed to clarify whether duration of targeted temperature management influenced LP protein levels, and we further examined whether LP proteins were associated with 30-day mortality. We included 82 patients resuscitated from out-of-hospital card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…14 This might be due to release of damage associated molecular patterns (DAMPs) from injured cells followed by a chain of injurious events 15 leading to activation of complement signalling pathways, in particular the lectin pathway. 16 While the aforementioned study showed no relation of lectin pathway activation and outcome, this study confirms that the end-product of complement system activation sC5b-9 is associated with poor outcome. TTM33 treatment of OHCA patients leads to suppression of complement activation with return to levels above reference limit after rewarming 17 while one study reports that TTM33 lead to reduction of the regulatory protein Map19 of the complement lectin pathway compared to TTM36.…”
Section: Complement Activationsupporting
confidence: 46%
“…14 This might be due to release of damage associated molecular patterns (DAMPs) from injured cells followed by a chain of injurious events 15 leading to activation of complement signalling pathways, in particular the lectin pathway. 16 While the aforementioned study showed no relation of lectin pathway activation and outcome, this study confirms that the end-product of complement system activation sC5b-9 is associated with poor outcome. TTM33 treatment of OHCA patients leads to suppression of complement activation with return to levels above reference limit after rewarming 17 while one study reports that TTM33 lead to reduction of the regulatory protein Map19 of the complement lectin pathway compared to TTM36.…”
Section: Complement Activationsupporting
confidence: 46%
“…MASP-2 and MAp19 are splice variants from the same gene but the lack of MAp19 in OHCA patients does not coincide with deficiency of MASP-2. 8 Thus, low MAp19 levels is presumably not a result of lacking transcription from the gene, but, rather, a specific influence on the splicing process leading to generation of MAp19 protein, or an increased usage or binding of MAp19 already present in the systemic circulation. Notably, our finding of non-detectable levels of MAp19 in the early phase after OHCA is novel and, to the best of our knowledge, this may be unique for post-arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 Prior work has demonstrated that the lectin pathway may be activated in post-cardiac arrest patients and furthermore that MASP-2 proteins levels were higher compared with healthy controls. 8 The gene MASP2 encodes two proteins: MASP-2, which is an enzyme activating complement factor C4 and C2 in the lectin pathway, and the smaller protein mannan-binding associated protein of 19 kilo Dalton (MAp19). 9 The two proteins share domain structures that interact with the pattern recognition molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Coagulation/fibrinolysis proteases may act as natural C3 and C5 convertases • Thrombin efficiently cleaved C5 at a newly identified, highly conserved R947 site, generating previously undescribed intermediates C5(T) and C5b(T) • C5b(T)-9 membrane attack complex has significantly more lytic activity than with C5b-9 • Complement activation in the presence of thrombin leads to assembly of C5bT • Lectin pathway inhibitors may be beneficial in patients with coagulation abnormalities/bleeding and incomplete response to C5 blockade • This can be extended to DIC mediated TMA as dysregulated coagulation cascade triggers secondary complement activation and some genetic mutations have been isolated in DIC linking to alternative pathway dysfunction and coagulation cascade mutations Cardiac/vascular emergencies [83][84][85][86] :…”
Section: Complement Blocker With Potential Benefit Reasoning For Pote...mentioning
confidence: 99%